2016
DOI: 10.1038/s41598-016-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an enzyme and substrate selective inhibitor of ADAM10 using an exosite-binding glycosylated substrate

Abstract: ADAM10 and ADAM17 have been shown to contribute to the acquired drug resistance of HER2-positive breast cancer in response to trastuzumab. The majority of ADAM10 and ADAM17 inhibitor development has been focused on the discovery of compounds that bind the active site zinc, however, in recent years, there has been a shift from active site to secondary substrate binding site (exosite) inhibitor discovery in order to identify non-zinc-binding molecules. In the present work a glycosylated, exosite-binding substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 57 publications
3
84
0
Order By: Relevance
“…MSCs on TCP upregulated monocyte chemoattractant protein-1 ( CCL2 ), galectin-9 ( GAL9 ), and TNFα-stimulated gene 6 ( TNFAIP6 ) after an initial pulse stimulation (Figure 5d and Figure S13), which was consistent with previous studies on MSC polarization to an immunomodulatory phenotype. [31] The gene expression levels of PTGS2 and TNFAIP6 were further upregulated as the stiffness (G’) was increased in the Alg hydrogels (Figure 5c–d). The levels were also plotted versus loss angle at each G’, which showed a viscoelastic-dependent increase in expression at 0.5 and 2.5 kPa G’.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs on TCP upregulated monocyte chemoattractant protein-1 ( CCL2 ), galectin-9 ( GAL9 ), and TNFα-stimulated gene 6 ( TNFAIP6 ) after an initial pulse stimulation (Figure 5d and Figure S13), which was consistent with previous studies on MSC polarization to an immunomodulatory phenotype. [31] The gene expression levels of PTGS2 and TNFAIP6 were further upregulated as the stiffness (G’) was increased in the Alg hydrogels (Figure 5c–d). The levels were also plotted versus loss angle at each G’, which showed a viscoelastic-dependent increase in expression at 0.5 and 2.5 kPa G’.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we aim to study the carry-over effects of sublethal herbicides on the F1 generation of A. retroflexus L. as an invasive plant using parent plants in the vegetative or reproductive periods treated by atrazine or tribenuron-methyl, which are two commonly used herbicides in Chinese arable cereal crops 33 and also commonly used to control A. retroflexus in China 34, 35 . Our objectives were: (i) to determine whether there was a carry-over effect of atrazine and tribenuron-methyl on the F1 generation of A. retroflexus , (ii) to compare the germination and growth of the F1 generation of A. retroflexus treated with herbicides during different growth periods (vegetative and reproductive), and (iii) to determine if an increased sublethal dose to the parent plant increases the toxic effect on the F1 generation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been a shift from active site to a secondary substrate binding site (exosite) inhibitor discovery . We described enzyme‐ and substrate‐selective non‐Zn 2+ binding inhibitors of ADAM17 and ADAM10 (Figure ) which are currently being tested in several pre‐clinical disease models. Both ADAM10 (CID 3117694) and ADAM17 (compound 19 in) leads were discovered as a result of screening efforts using a glycosylated, exosite‐binding substrate based on the TNFα sequence .…”
Section: Adam Inhibitors: General Considerationsmentioning
confidence: 99%
“…We described enzyme‐ and substrate‐selective non‐Zn 2+ binding inhibitors of ADAM17 and ADAM10 (Figure ) which are currently being tested in several pre‐clinical disease models. Both ADAM10 (CID 3117694) and ADAM17 (compound 19 in) leads were discovered as a result of screening efforts using a glycosylated, exosite‐binding substrate based on the TNFα sequence . Mechanistic studies showed that both inhibitors acted via a non‐Zn 2+ binding mechanism, which explained their selectivity toward ADAM10 and ADAM17 (Table ).…”
Section: Adam Inhibitors: General Considerationsmentioning
confidence: 99%